Deep brain stimulation and other surgical modalities for the management of essential tremor. (2nd August 2020) - Wang, Kai-Liang; Ren, Qianwei; Chiu, Shannon; Patel, Bhavana; Meng, Fan-Gang; Hu, Wei; Shukla, Aparna Wagle
ABSTRACT: Introduction: Surgical treatments are considered for essential tremor (ET) when patients do not respond to oral pharmacological therapies. These treatments mainly comprise radiofrequency (RF) thalamotomy, gamma knife radiosurgery (GKRS), deep brain stimulation (DBS), and focused ultrasound (FUS) procedures. Areas covered: We reviewed the strengths and weaknesses of each procedure and clinical outcomes for 7 RF studies (n = 85), 11 GKRS (n = 477), 33 DBS (n = 1061), and 13 FUS studies (n = 368). A formal comparison was not possible given the heterogeneity in studies. Improvements were about 42%–90% RF, 10%–79% GKRS, 45%–83% DBS, 42%–83% FUS at short-term follow-up (<12 months) and were about 54%–82% RF, 11%–84% GKRS, 18%–92% DBS, and 42%–80% FUS at long-term follow-up (>12 months). Expert opinion: We found DBS with inherent advantages of being an adjustable and reversible procedure as the most frequently employed surgical procedure for control of ET symptoms. FUS is a promising procedure but has limited applicability for unilateral control of symptoms. RF is invasive, and GKRS has unpredictable delayed effects. Each of these surgical modalities has advantages and limitations that need consideration when selecting a treatment for the ET patients.